The Human Language: a structure plus a code or a dynamic, multimodal and semiotically heterogeneous communicative system? - Scotto, Silvia Carolina (Analysis. Journal of Philosophical Research, 2020)
Comparative studies about human language and animal communication systems, so as the research field about language evolution, have stimulated a specific reflection about the distinctive features of human language. My aim is to examine the model of the design features proposed by Charles Hockett, whose influence has been significant on both aforementioned areas. My purpose is to highlight how the presuppositions, under which the preeminence of the structure over the function and of the features of the code over the cognitive abilities of its users are based (both common to other formal approaches that were the dominant ones in linguistics), turn it into a theoretically ineffective tool on both research fields. In particular, I will object to the role that this model has attributed to the first two design features: the vocal-auditory channel and the arbitrariness. Finally, I will contrast it with the language usage-based approaches, supported by the opposite presuppositions. These approaches characterize language as a “mosaic” of cognitive, individual and social, abilities that manifest on a variety of vehicles and modalities; therefore, these provide more suitable theoretical tools than formal approaches to explain language evolution, so as its differences and similarities to animal communication systems.